Characteristics and Outcomes of Hip Fracture Patients Hospitalized in an Orthogeriatric Unit Versus an Orthopedic Department: A Retrospective Cohort Study. (7th January 2021) - Bugaevsky, Yulia; Levy, Yochai; Hershkovitz, Avital; Ocheretny, Irena; Nissenholtz, Adaya; Cooper, Lisa; Weissman, Yaara Leibovici; Weiss, Avraham; Velkes, Steven; Beloosesky, Yichayaou
Introduction: Hip fractures are a significant health risk in older adults and a major cause of morbidity, functional decline and mortality. Our aim was to compare clinical outcomes of older patients hospitalized in an ortho-geriatric (OG) unit to those hospitalized in an orthopedic department (OD) for surgical treatment of a hip fracture. Methods: A retrospective cohort study of hip fractured patients hospitalized between 2015-2016 in a single tertiary university-affiliated medical center. Included were patients aged 65 and older who had undergone hip fracture surgery and were admitted to either a geriatric or orthopedic ward. Results: 441 patients met the inclusion criteria (195 in the OG unit, 246 in the OD); 257 were transferred to an affiliated geriatric center hospital (107 from the OG unit and 127 from the OD) for rehabilitation. Patients in the OG unit were older, more cognitively and functionally impaired and with more comorbidities. The 1-year mortality rate was significantly lower in the OD group (OR 0.32, CI 95% 0.19-0.53, p < 0.001), however, after propensity matching, the 30-day and 1 year mortality rates were similar in both groups. No difference was found in the rehabilitation length of stay between the groups. The functional independence measure improvement was similar in both groups, with a non-significant trend toward better functional improvement among OG unit patients. Conclusions: Despite the higher complexity of patients, worse baseline functional capacity in the OG unit, improvement after rehabilitation was similar in both groups. These results demonstrate the advantages of the OG unit in treating and stabilizing frail older adults, thus maximizing their chances for a successful recovery after hip fractures. Level of Evidence: Level IV